(untitled) (The Pakistan Development Review, 2006)
The book “Communication of Innovations” comprises of ten essays that focus and highlight the ideas and works of a highly renowned student and proponent of diffusion of innovations, communication networks, and social change—Everett Rogers. Each chapter of the book discusses different aspects of Rogers’s dynamic personality, his individual and remarkable ways of working and advancing in his field. This book presents introductory remarks to Everett Rogers’ personality. His beginnings in the field of communication of innovation, his focus on diffusion of innovation, his optimism, his main intellectual contribution, the combination of the diffusion of innovation models and the main purpose of writing this book to ‘honour the memory and contributions’ of Rogers is also elaborated.